Saturated magnetization and glass forming ability of soft magnetic Fe-based metallic glasses. (May 2017) - Huang, B.; Yang, Y.; Wang, A.D.; Wang, Q.; Liu, C.T.
Abstract: Saturated magnetization ( B s ) and glass forming ability (GFA) are two important attributes of soft magnetic metallic glasses (MGs), both of which are affected by the local short-range order in amorphous structures. Based on the notion of free electron transfer, we propose a set of simple rules for the calculation of B s from the chemical composition of soft magnetic Fe-based alloys. Through the comparison of the experimentally measured B s and theoretically calculated B s, we show that the soft magnetic Fe-based MGs can be generally categorized into two types: one has its GFA correlated positively with the ferromagnetic weakness and the other has its GFA correlated negatively with the ferromagnetic weakness. Finally, the structural mechanisms behind these correlations are discussed. Highlights: A model for saturated magnetization is proposed based on charge transfer. Connection of magnetic weakness and glass forming ability is revealed. Evolution of local atomic packing underlies the above connection.